Stimulation Of Development of Social Emotional Aspects of Early Children Through Story Method - Azizah, Nurul; Diana, Raden Rachmy (STAI MA'ARIF MAGETAN, INDONESIA, 2022)
Socio-emotional development is an important aspect that must be stimulated in early childhood. Socio-emotional development in early childhood will be the foundation for children to become responsible, caring and productive adults. The story method is one way to stimulate the socio-emotional development of early childhood. This research method uses descriptive qualitative research to see and understand the subject and object under study. The subjects in this study were housewives in the city of Magetan as many as five people who had early childhood. By using the method of observation, interviews and self- report in the data collection process, as well as using the method of studying literature from various sources of journals, books, and supporting research results. Stimulation of social-emotional aspects of development through the story method has a good impact, although it is not optimal due to several obstacles experienced by parents in applying this story method. Socio- emotional development in early childhood education has several indicators which are divided into three aspects, namely aspects of self-awareness, aspects of a sense of responsibility for oneself and others and aspects of prosocial behavior.